基于MFBD的汽车多楔带动力学仿真分析研究 - 李占国; 张云贺; 史尧臣 (Jixie chuandong)
Aiming at the PK type automotive V-ribbed belt,using the CATIA software,the automotive V-ribbed belt model and the pulleys 3D model is created,automotive V-ribbed belt mesh is based on the ANSYS software,and imports into the multi-body dynamics RecurDyn software to build up the dynamic simulation model of the automotive V-ribbed belt transmission through the MFBD（more flexible body dynamics） techniques.The transmission performance of the automotive V-ribbed belt,contact strength of belt surface and tension stress are analyzed.It gives the stress distribution between the belt and the gear belt,and the distribution state of the tensile stress.It provides a digital simulation analysis and design method to design the automotive V-ribbed belt shape,analysis the transmission performance,select the rubber and the powerful layer.